(untitled) (Afaq Lughawiyyah, 2024)
This research seeks to study the translation of Arabic adjective clause and relative pronoun to Malay language to find out the similarities and differences between the two. It also seeks to study the translation strategies used by the translators to translate the clause. In this regard, the research identifies and extracts adjective clauses and relative pronouns from Kalilah wa Dimnah and its translation by Sitti Hadijah Mappeneding, analyses the translation, and identifies translation strategies used to translate the text. This research uses the descriptive-analytical method by means of content analysis where data were gathered from a chapter of Kalilah wa Dimnah, and the framework for the translation analysis is based on the Vinay and Darbelnet’s model. The findings concluded that there are 20 adjective clauses and 32 relative clauses in the chosen chapter, and the translation of the two clauses have more similarities than differences, as both are in the same grammatical function in Malay language which is ayat majmuk pancangan relatif. The translation strategies used also involve the same procedures based on the Vinay and Darbelnet’s model which are transposition and modulation. Hence, adjective clause and relative clause in Arabic are related in terms of grammar and meaning.